2018
DOI: 10.1007/s12325-018-0779-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Management of Women with Postmenopausal Osteoporosis Treated with Denosumab: A Prospective Observational Study in the Czech Republic and Slovakia

Abstract: IntroductionOsteoporosis is characterized by low bone mineral density (BMD) and an increased risk of fracture. In randomized controlled trials, denosumab has been shown to significantly reduce the fracture risk in women with osteoporosis. However, little is known about the real-world management of women who are prescribed denosumab.MethodsThis multicenter, prospective, observational real-world study in the Czech Republic and Slovakia evaluated the baseline characteristics and clinical management of women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The prevalence of risk factors for fracture observed in our study population, such as smoking status [15], mean BMI [16,17], the number and type of comorbidities [18,19], age, and cause of menopause onset [17,18,20], was similar to previous studies, validating these risk factors.…”
Section: Original Papersupporting
confidence: 89%
See 2 more Smart Citations
“…The prevalence of risk factors for fracture observed in our study population, such as smoking status [15], mean BMI [16,17], the number and type of comorbidities [18,19], age, and cause of menopause onset [17,18,20], was similar to previous studies, validating these risk factors.…”
Section: Original Papersupporting
confidence: 89%
“…These data reflect the local reimbursement criteria at the time of the study [13]. Studies from the Czech Republic and Slovakia also reported that reimbursement criteria for denosumab impacted the baseline characteristics of enrolled patients [17].…”
Section: Original Papermentioning
confidence: 52%
See 1 more Smart Citation
“…In conclusion, this is the first study of real-life results of denosumab treatment in osteoporotic Turkish population in real-life setting of denosumab treatment. These studies further give information about drug adherence and effectiveness in the real-life setting [19][20][21]26]. According to the results of this current study, denosumab is an effective treatment for osteoporosis with similar effectivity in different comorbid conditions with non-significant side effects.…”
Section: Discussionmentioning
confidence: 71%
“…In recent real-life persistence data about denosumab, persistence was 71% in a 7.5 year of follow-up, which was higher from other studies. The authors attributed this to positive motivation practices by describing the results of treatment with patients during outpatient control [21]. The osteoclastic effects of denosumab reverse with cessation of treatment and increase in fracture risk was shown with studies [13,14].…”
Section: Discussionmentioning
confidence: 99%